Neurobehavioral Effects of LSVT® LOUD on Auditory-Vocal Integration in Parkinson’s Disease: A Preliminary Study - Li, Yongxue; Tan, Mingdan; Fan, Hao; Wang, Emily Q.; Chen, Ling; Li, Jingting; Chen, Xi; Liu, Hanjun (Frontiers in Neuroscience, 2021)
Individuals with Parkinson’s disease (PD) are impaired in auditory-vocal integration, characterized by abnormal compensatory responses to auditory feedback errors during self-monitoring of vocal production. The present study examined whether auditory feedback control of vocal pitch production in PD can benefit from Lee Silverman voice treatment (LSVT® LOUD), a high effort, intensive speech treatment for hypokinetic dysarthria in PD. Before and immediately after LSVT LOUD, twelve individuals with PD were instructed to produce sustained vowel sounds while hearing their voice unexpectedly pitch-shifted by -200 cents. Their vocal responses and event-related potentials (ERPs) to pitch perturbations were measured to assess the treatment outcomes. A group of 12 healthy controls were one-to-one pair matched by age, sex, and language. Individuals with PD exhibited abnormally enhanced vocal and event-related potential (ERP) P2 responses to pitch perturbations relative to healthy controls. Successful treatment with LSVT LOUD, however, led to significantly smaller and faster vocal compensations that were accompanied by significantly larger P2 responses. Moreover, improved vocal loudness during passage reading was significantly correlated with reduced vocal compensations for pitch perturbations. These preliminary findings provide the first neurobehavioral evidence for beneficial effects of LSVT LOUD on impaired auditory-vocal integration associated with PD, which may be related to improved laryngeal motor functions and a top-down modulation of the speech motor network by LSVT LOUD.